Pelatihan Aplikasi Canva dalam Membuat Aksi Nyata Guru Serta Pembuatan Konten Pembelajaran Sebagai Upaya Meningkatkan Kompetensi Guru di Desa Klatakan - Lusi Endang Sri Darmawati; Nur Hasanah; Siti Seituni; Siti Muhafizah (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2024)
This service activity introduces or trains teachers in utilizing the Canva application which can be used by teachers to create interesting content related to learning and Canva can also help teachers. This application also provides various design examples to use, which are free to use and there is also paid Canva. Canva can be accessed via Canva web or Canva application. The stages in this service activity are the observation stage first, the planning stage according to the partner's needs, determining the activities, the material delivery stage, discussion, the training stage in which the teachers directly practice and create learning content.. The service methods used include presentations and demonstrations for activity participants. The result of this activity was that it succeeded in contributing to their understanding of what was delivered, both material and training. So it can be a provision for teachers to complete learning content and real action.